Self-selection into economics experiments is driven by monetary rewards - Johannes Abeler; Daniele Nosenzo (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2013)
Laboratory experiments have become a wide-spread tool in economic research. Yet, there is still doubt about how well the results from lab experiments generalize to other settings. In this paper, we investigate the self-selection process of potential subjects into the subject pool. We alter the recruitment email sent to first-year students, either mentioning the monetary reward associated with participation in experiments; or appealing to the importance of helping research; or both. We find that the sign-up rate drops by two-thirds if we do not mention monetary rewards. Appealing to subjects' willingness to help research has no effect on signup. We then invite the so-recruited subjects to the laboratory to measure a range of preferences in incentivized experiments. We do not find any differences between the three groups. Our results show that student subjects participate in experiments foremost to earn money, and that it is therefore unlikely that this selection leads to an over-estimation of social preferences in the student population.
Keywords: C90; D03; 330; methodology; selection bias; laboratory experiment; field experiment; otherregarding behavior; social preferences; social approval; experimenter demand